2016
DOI: 10.21037/atm.2016.12.28
|View full text |Cite
|
Sign up to set email alerts
|

Inertia based microfluidic capture and characterisation of circulating tumour cells for the diagnosis of lung cancer

Abstract: Background: Routine clinical application of circulating tumour cells (CTCs) for blood based diagnostics is yet to be established. Despite growing evidence of their clinical utility for diagnosis, prognosis and treatment monitoring, the efficacy of a robust platform and universally accepted diagnostic criteria remain uncertain. We evaluate the diagnostic performance of a microfluidic CTC isolation platform using cytomorphologic criteria in patients undergoing lung cancer surgery.Methods: Blood was processed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Peripheral blood was then collected in parallel and processed identically. The blood sample was processed using the ClearBridge ClearCell FX system TM (ClearBridge Biomedics, Singapore) 29 . Samples were further negatively sorted to remove the CD45 positive monocytes using EasySep™ Human CD45 Depletion Kit (18259RF, StemCell, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral blood was then collected in parallel and processed identically. The blood sample was processed using the ClearBridge ClearCell FX system TM (ClearBridge Biomedics, Singapore) 29 . Samples were further negatively sorted to remove the CD45 positive monocytes using EasySep™ Human CD45 Depletion Kit (18259RF, StemCell, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Ohnaga reported that the CTC chip was able to isolate EC cell lines spiked in whole blood, and that its recovery rate was over 70% [ 33 ]. Following the CTC chip, many kinds of microfluidic platforms have been developed, such as ClearCell FX, based on size, deformability, and inertia separation [ 34 ]; CTC-iChip, based on positive and negative enrichment with size-based separation [ 35 ]; IsoFlux, based on automated continuous flow with EpCAM beads [ 19 ]; magnetic sifter, based on vertical flow configuration [ 36 ]; and vortex, based on inertial microfluidics and laminar microscale vortices without a red blood cells (RBC) lysis buffer [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Over the past years, the concept of liquid biopsies has been introduced as an alternative to conventional tissue biopsy. Circulating tumour cells (CTCs) are cells that invade into the bloodstream from the primary tumours in the abdominal cavity ( 41 , 42 ). These cells are different to normal circulating blood cells and express tumour-specific characteristics.…”
Section: Discussionmentioning
confidence: 99%